Decomposing the tensor product of complete graphs into cycles of length eight. Issue 4 (19th May 2022) - Akwu, Abolape Deborah; Oyewumi, Opeyemi
Abstract: We give the necessary and sufficient conditions for the decomposition of the tensor product Km × Kn, m, n ≥ 2, into cycles of length eight.